Development and evaluation of recombinant vector cells carrying cell wall surface anchor family proteins as a vaccine against streptococcosis in red hybrid tilapia (Oreochromis SPP) - Mansor, Nur Nazifah (2013)
Tilapia is one of the most common cultured fish in many countries. However,productions of tilapia might decrease due to various diseases, including streptococcosis that can kill 100% of the fish. In Malaysia, outbreaks of streptococcosis are frequently observed during the dry months, particularly between April and August when the water temperature is high. Streptococcosis in fish is caused by either Streptococcus agalactiae or S. iniae. Although vaccination is practiced to control streptococcosis, the protection remains unclear. Thus, this project attempted to develop and evaluate recombinant cell for vaccine preparation to improve vaccine efficacy against streptococcosis. The hypothesis of this study are major outer surface protein of Streptococcus agalactiae is suitable as vaccine candidate and can be cloned and expressed in the Escherichia coli prokaryotic system to produce the recombinant vaccine. The newly develop feed based recombinant vaccine can elicit certain level of systemic and mucosal antibody and gave protection against Streptococcosis in red hybrid tilapia. The outer surface proteins (OSPs) of S. agalactiae isolated earlier from fish that died of streptococcosis were extracted, purified and characterized. The 48kDa protein band was found to be the most antigenic following SDS-PAGE and Western immunoblotting methods. Therefore, the 48kDa protein band was selected for further studies as a vaccine candidate. The 48kDa band was processed for N-terminal sequencing, and the results revealed that the protein was the cell wall surface anchor family protein of the outer surface protein (OSP) of S. agalactiae, which was encoded by a gene of approximately 1263bp in size. The DNA gene was amplified by the polymerase chain reaction (PCR) method, purified and cloned in pET-32 Ek/Lic vector. The successful clones were then transformed into Novablue Escherichia coli strain before the positive clones were screened for the end product of 1335bp; the vector contributed 72bp. Plasmid extraction was performed prior to the expression of the cell wall surface anchor family protein in the BL21 (DE3) Escherichia coli. Overnight Express™ Autoinduction system 1 (Novagen, USA) was used in expression. Successful protein expression was analysed by SDSPAGE and western immunoblotting and was found to be approximately 65.8kDa, consisted of the 48kDa cell wall surface anchor family protein and the 17.8kDa of tagged protein.